Textile-Based Flexible Supercapacitors - Altin, Yasin; Çelik Bedeloğlu, Ayşe (CRC Press, 2022)
With the increase in smart and wearable electronic applications, it has become important to meet the energy demands of these products with flexible and wearable energy storage technologies. Conventional energy storage techniques have difficulty meeting critical requirements, such as flexibility and safety, for wearable electronics applications. Among the textile-based energy storage applications, flexible textile-based supercapacitors stand out due to their advantages, which include flexibility, light in weight, environmentally friendly, long cycle life, and fast charge/discharge. Carbon-based materials (activated carbon, graphene, carbon nanotube, carbon nanofiber, etc.), metal oxides/nitrides/sulfides, conductive polymers (polyaniline, polythiophene, polypyrrole, PEDOT: PSS, etc.), and their combinations are used as electrode materials in supercapacitor applications. Textile-based supercapacitors are developed both by spinning/drawing these electrode materials into a textile form, such as graphene yarn, carbon nanotube yarn, etc., and by applying them on various textile substrates. In this chapter, materials used in textile-based supercapacitors, application techniques of these materials, and textile-based supercapacitor forms are discussed in detail. © 2022 selection and editorial matter,[Ram K. Gupta, Tuan Anh Nguyen; individual chapters, the contributors.